Effect of two drainage rates on cucumber (Cucumis sativus) under greenhouse conditions (UNED Research Journal, 2023)
“Effect of two drainage rates on cucumber (Cucumis sativus) under greenhouse conditions”. Introduction: Drainage rate is an important factor in hydroponic production. Objective: to evaluate the effect of two drainage rates on the yield and quality of cucumber (cv. Modan) under greenhouse conditions in the dry and rainy seasons. Methods:  We used fertigation and coconut fiber as substrate. Results: In all quality categories, there were no statistically significant differences between irrigation rates for the number of fruits per m2, fruit weight and yield; while the percentage of total soluble solids was higher at 10% irrigation. The rainy season cucumbers had more total fruits per m2; commercial fruit weight; and total, second and third quality yield. Conclusion: For this conditions, a 10% irrigation rate will save water and nutrients, and increase crop profitability.
Keywords: leaching franction; electric conductivity; salinity; sustainability; climate change